Evaluation of okra (Abelmoschus esculentus) genotypes for yield and yellow vein mosaic disease - S.S. SOLANKEY*; ANUPAM ADARSH, AMIT KUMAR, R.B. VERMA (Indian Phytopathology, 2015)
Yellow vein mosaic disease of okra is caused by Okra yellow vein mosaic virus (OYVMV) consisting of monopartite DNA molecule and a beta satellite (DNA component). Infection of 100% plants in a field is very usual and yield losses range from 50 to 94%, depending on stage of crop growth at which infection occurs and its vector whitefly (Bemisia tabaci Gen.). Thus, 30 diverse okra genotypes including 4 national check (VRO 6, Pusa Sawani, Arka Anamika, and Arka Abhay) were grown in RCBD during rainy season, 2013-14, for 14 diverse traits. The magnitude of phenotypic coefficient of variation (PCV) was higher than that of genotypic coefficient variation (GCV) for all the traits. High value of PCV with corresponding high value of GCV were observed for number of branches, number of fruit-plant, fruit yield plant, per cent disease incidence (PDI) and coefficient of infection (CI). This indicated that selection of genotypes on the basis of these characters is desirable. The genotypes, viz. IIHR 129, IIHR 123, IIHR 112, IC 14845B and IC 14600, IIHR 120, IIHR 53, IIHR 113, were found promising for most of the yield-contributing traits; whereas among check varieties, VRO 6 and Arka Anamika, performed better. These genotypes could be used further in hybrid breeding programme, due to their high yield and lower OYVMV incidence.